2013
DOI: 10.1160/th13-10-0882
|View full text |Cite
|
Sign up to set email alerts
|

miR-223: sailing to terra incognita for microRNAs in platelets

Abstract: Insight miR-223 plays a remarkably modest role in thrombopoiesis and platelet function does not depend upon miR-223

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, both mature and passenger strands of miR-33 have been shown to affect lipid and even glucose metabolism [19]. Last but not least, miR-223, besides affecting lipid metabolism on the cellular level, is the best example of miR highly abundant in HDL particles [26], microvesicles and exosomes [27] and even platelets [28]. The exact roles of the three abovementioned and other miRs will be described in more detail in this chapter.…”
Section: Micrornas Involvement In Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both mature and passenger strands of miR-33 have been shown to affect lipid and even glucose metabolism [19]. Last but not least, miR-223, besides affecting lipid metabolism on the cellular level, is the best example of miR highly abundant in HDL particles [26], microvesicles and exosomes [27] and even platelets [28]. The exact roles of the three abovementioned and other miRs will be described in more detail in this chapter.…”
Section: Micrornas Involvement In Lipid Metabolismmentioning
confidence: 99%
“…Lastly, miR-223 was shown to be involved in platelet function [28] and reactivity to anti-aggregation treatment—in patients with low-response to clopidogrel therapy, platelet miR-223 levels were significantly lower compared to normal-responders [113]. Lower levels of miR-223 were also observed in plasma of low-responders [114]; however, most recently Chyrchel and coworkers presented a study that argues against the notion of low plasma miR-223 as a marker of platelet responsiveness to dual antiplatelet therapy [115].…”
Section: Mir-223: “The Messenger”mentioning
confidence: 99%
“…This result is of special interest, as platelets contain high levels of miR‐223 and are a major source of plasma miR‐223 . In this sense, Halken and De Windt hypothesized that certain platelet miRNAs ‘may act in target cells other than the ones where they are produced', a proposal that deserves deeper research . Actually, a report published a short time later showed that platelet microvesicles formed after thrombopoietin or thrombin activation contain high levels of miR‐223 that are able to induce the formation of advanced glycation end‐products, inducing human umbilical vein enothelial cell (HUVEC) apoptosis by targeting insulin‐like growth factor 1 receptor .…”
Section: Mirna As a Regulator Of The Hemostatic Systemmentioning
confidence: 99%
“…A number of highly expressed miRNA have been characterised in human platelets, some of which are involved in myeloid cell differentiation, megakaryocytopoiesis and thrombopoiesis. miR-223 has been identified as the most highly expressed platelet miRNA [38,43,44] and has roles in thrombopoiesis and megakaryocyte differentiation [24]. miR-223 regulates ADP P2Y 12 , a target for existing anti-platelet drug therapy.…”
Section: Platelet Epigenetics 21 Platelet Mirnamentioning
confidence: 99%